Trend inflation and inflation persistence in the New Keynesian Phillips curve - Timothy Cogley; Argia M. Sbordone (Federal Reserve Bank of New York, 2006)
The New Keynesian Phillips curve (NKPC) asserts that inflation depends on expectationsof real marginal costs, but empirical research has shown that purely forward-looking versions of the model generate too little inflation persistence. In this paper, we offer a resolution of the persistence problem. We hypothesize that inflation is highly persistent because of drift in trend inflation, a feature that many versions of the NKPC neglect. We derive a version of the NKPC as a log-linear approximation around a time-varying inflation trend and examine whether it explains deviations of inflation from that trend. We estimate the NKPC parameters jointly with those that define the inflation trend by estimating a vector autoregression with drifting coefficients and volatilities; the autoregressive parameters are constrained to satisfy the restrictions imposed by the NKPC. Our results suggest that trend inflation has been historically quite volatile and that a purely forward-looking model that takes these fluctuations into account approximates well the short-run dynamics of inflation.
Keywords: E31; 330; inflation persistence; Phillips curve; time-varying VAR; Inflation; New-Keynesian Phillips Curve; VAR-Modell; USA